A COVID-19 como doença ocupacional - Carvalho, Bruna Larissa Feitosa de (2024)
The emergence of Covid-19 in China brought significant changes to people's routines around the world, being elevated to pandemic status. In Brazil, the disease spread quickly, making it necessary to rearrange the population's habits and adapt rules to the health crisis. The disease was detected in millions of people in the country, killing a significant percentage. In this sense, to avoid an increase in the number of sick people, due to the potential worsening of the patients' clinical condition and the viral nature of the disease, which has rapid and imprecise contamination, experts recommended social isolation (lockdown) and carrying out work at home. (home office). However, some workers, due to the activity they carry out, especially those in the health sector, were more exposed to SARS-CoV-2. With the mass adoption of such measures by the population, little by little, it was possible to return to face-to-face activities, albeit gradually, with the indication of the use of personal protective equipment. Even so, there remained concern among workers and employers that Covid-19 could be contracted in the workplace and, in this sense, be considered an occupational disease. The objective of this work is to analyze the entire context of the problem, reflecting on the need to make rights and legal principles more flexible in the face of the instability resulting from the pandemic